Implementasi Kualitas Pelayanan terhadap Kepuasan Pengunjung di Bali Zoo Gianyar - Pradipta Nugraha; Kanah Kanah; Ni Luh Eka Armoni; Elvira Septevany (Yayasan Literasi Sains Indonesia, 2026)
This study aims to examine the implementation of service quality and its influence on visitor satisfaction at Bali Zoo, Gianyar. The service quality in this research is analyzed using the five dimensions of the SERVQUAL model: tangibles, reliability, responsiveness, assurance, and empathy. The study employs a descriptive quantitative approach with a survey method conducted on 100 respondents who visited Bali Zoo. The data analysis techniques used include descriptive statistical analysis, validity and reliability tests, correlation analysis, simple linear regression, and t-test, with the assistance of SPSS software.The results indicate that all five dimensions of service quality are categorized as highly implemented, with the highest average score found in the empathy dimension, reaching 48.376. The correlation analysis shows a significant positive relationship between service quality and visitor satisfaction, with a correlation coefficient of 0.690. Regression analysis reveals that service quality has a significant influence on visitor satisfaction (Sig. 0.000 < 0.05), contributing 47.6% to the visitor satisfaction variable. Based on these findings, it is recommended that Bali Zoo maintain its strength in the empathy dimension while making improvements in the tangible and reliability aspects to enhance overall visitor satisfaction.